Analisis Tingkat Kesehatan Bank Syariah Indonesia (BSI) Dengan Metode RGEC Pada Periode 2019-2022 - Awaliah, Siti Farika Nurul; Suhartini, Nani; Atiah, Isti Nuzulul (Syi`ar Iqtishadi : Journal of Islamic Economics, Finance and Banking, 2023)
This study aims to determine the level of bank health at PT. Bank Syariah Indonesia during 2019-2022 based on the RGEC method consisting of risk profile, good corporate governance, earnings and capital. The data collection method used is non-participant observation by means of documentation. Descriptive analysis techniques are guided by Bank Indonesia Circular Letter No. 13/24/DPNP concerning Health Level Assessment of Commercial Banks. The results showed that PT. BSI's health level bank for the 2019 period is in the healthy category with a value of 83% being in the PK-2 composite predicate. This year was the beginning of the Covid-19 pandemic, but from the overall assessment and analysis carried out, it turned out that it did not have much effect on BSI's health level. In 2020-2022 BSI experienced an excellent level of health. That is 86% in PK-1 for 2020 and 91% in PK-1 for 2021 and 2022..